Reminiscences of unforgettable times of my collaboration with Nikolai N. Bogolubov (Jr.) - Prykarpatsky, A.K. (Condensed Matter Physics, 2010)
Author devotes these recollections to his Teacher and Friend Prof. Nikolai N. Bogolubov (Jr.) in honor of his 70th birthday.